Magnetic solid‐phase extraction based on carbon nanosphere@Fe3O4 for enantioselective determination of eight triazole fungicides in water samples. Issue 9 (12th February 2019) - Wang, Zhaokun; Wang, Xia; Li, Shuang; Jiang, Zhen; Guo, Xingjie
Abstract: In this work, a carbon nanosphere decorated by Fe3 O4 nanoparticles was prepared, characterized and used as the magnetic adsorbent. Eight commonly used chiral triazole fungicides, including penconazole, uniconazole, paclobutrazol, triazolone, tebuconazole, hexaconazole, triticonazole and epoxiconazole were extracted from two environmental water samples (river water and lake water) by magnetic solid‐phase extraction, followed by the enantiomeric analysis on a Chiralpark IC column coupled with a triple quadrupole mass spectrometry to evaluate their possible stereoselective degradation occurring in the water samples. The possible factors affecting the extraction performance, such as amount of used adsorbents, pH and ionic strength of water solution, types and volumes of desorption solvents were systematically investigated. Under the optimum conditions, extraction yields of eight triazole fungicides were above 80% and the concentration factors were as high as 1000. Method detection and quantification limits for the enantiomers of eight triazole fungicides were in the range of 0.56–6.95 ng/L. Satisfactory accuracy (relative recovery 77.8–93.5%), good intraday precision (RSD 4.3–9.8%) and interday precision (RSD 3.1–7.9%) were also obtained. The developed method provided the simplicity of operation, rapidity and high enrichment factor, which can be used to monitor and evaluate the behavior of the individual enantiomer of chiral triazole fungicides.